“Fake News” or Real Science? Critical Thinking to Assess Information on COVID-19 - Puig, Blanca; Blanco-Anaya, Paloma; Pérez-Maceira, Jorge J. (Frontiers in Education, 2021)
Few people question the important role of critical thinking for students becoming active citizens, however the way science is taught in schools continues to be more oriented towards ‘what to think’ rather to ‘how to think’. Researchers understand critical thinking as a tool and a higher order thinking skill necessary for being an active citizen when dealing with socio-scientific information and making decisions that affect human life, as the pandemic of COVID-19 manifests. The outbreak of COVID-19 has been accompanied by what the World Health Organization (WHO) has described as a “massive infodemic”. Fake news regarding the disease were spread through the social media creating confusion and disinformation. This paper reports on an empirical study carried out during the lockdown in Spain (March-May 2020) with a group of secondary students (N=20) engaged in diverse online activities that required them to practice critical thinking and argumentation for dealing with coronavirus information and disinformation. The main goal is to examine students' competence to engage in argumentation as critical assessment in this context. Discourse analysis allows exploring the arguments and criteria appealed by students to assess COVID-19 news headlines. The results show that participants were capable to identify true and false headlines and assess the credibility of headlines appealing to different criteria; although most arguments were coded as basic epistemic level of assessment and only a few in the high level appealing to the criterion of scientific procedure when assessing the news headlines.